WITNESSING LIKE A USER: MOBILE NOTIFICATIONS AND THE LAYERED CONSTRUCTION OF MEDIATIZED TERRORISM - Fitzgerald, Andrew Arthur (AoIR Selected Papers of Internet Research, 2021)
This paper study the imbrication of data-driven devices and platform infrastructures and the mediatized construction of terrorist attacks. It analyzes the role of smartphone push notifications and technical affordances of “layering” media across diverse media devices and platforms in users’ mediatized life (e.g. screenshotting a tweet, posting it to Facebook, and users’ commenting on the post), and these platform and device features role in co-constructing terrorist attacks as datafied media events along with mobile media posts and reactions by users and formal news accounts and aggregations by media outlets. Using a data collection framework that logs screenshots of participants’ mobile media devices every five seconds over the course of longitudinal studies, I qualitatively observe screenshots capturing the mobile media usage of 16 subjects from late May to late June 2017, including media relating to two terrorist attacks in the UK. This paper illustrates the role of mobile device and datafied platform features in the sparking of mediatized microrituals and the broader construction of terrorist attacks as datafied media events. It also highlights the layering of mediatization, wherein the above-mentioned interface elements often migrate with a given media object across platforms within a single mobile environment on the user-end, and as it is layered with the users’ in-person contexts beyond the screen. The study of mediatized terrorism, therefore, must be understood across these layers, necessitating further empirical exploration and conceptual development.